Integrity As The Identity Of Educators In The School Arena - AB, Suryo; Purwanto, Agung; Budi, Setia (IJBLE Scientific Publications Community Inc., 2023)
This research to describe the importance of building the self-integrity of teaching staff as an effort to build a positive and productive culture in the school environment. This research uses a qualitative approach relying on secondary data as strategy of inquiry. The secondary data collection carried out was not supported by interview data, surveys, observations and other specific data collection techniques. The use of secondary data was chosen because researchers were limited in collecting data and information directly which was too extensive to do. The literature review method is useful in the context of time, cost and energy efficiency because the data is already available, so it is more worthy to do. The results of this research show that educators are actors of change who are tasked with instilling values ​​in their students. So, it is important for educators to understand the concept of self-integrity which needs to be continuously inculcated as part of daily practice, especially in the school environment